DECISION SUPPORT SYSTEM FOR SELECTING THE BEST AIRLINE AT KUALANAMU AIRPORT USING THE WEIGHT PRODUCT METHOD - Azhari, Muhammad Ezam; Elsera, Marina; Nurjamiyah (Cattleya Darmaya Fortuna, 2025)
Many airlines still face various problems even though the development of the Indonesian aviation service industry continues to grow. The many choices and considerations in choosing an airline often confuse customers because each airline has its advantages. Air transportation is an option for consumers who want to travel long distances in a shorter time compared to sea and land transportation. The diversity of airlines often makes it difficult for airline users to choose an airline. The purpose of this study is to build a decision support system using the weight product method that can be used to help prospective users make wise airline selection decisions. The weight product method decision support system is one of the decision-making methods that considers several criteria or factor weights. This method is often used in situations where a decision must be made based on several different factors, and each factor has a different weight.